Providing Alternative Understandings of School Equivalency Trough Literacy and Storytelling - Syahid Abdulloh; Zulfa Sakhiyya; Hendi Pratama (Universitas Negeri Semarang, 2023)
Omah Dongeng Marwah, a library community and school equivalency organizer, distinguishes itself from typical school equivalency institutions, which are often seen as mere diploma publishers. Through storytelling, book discussions, and nurturing students' talents, ODM offers an innovative outlook on literacy practices. This research explores the profound impact of ODM's immersive storytelling along with diverse literacy practices to give alternative understandings of school equivalency. Using qualitative research, I investigated why and how Omah Dongeng Marwah Kudus challenges the stigma associated with school equivalency through storytelling and literacy practices. Critical Discourse Analysis was employed to understand the social dimensions influencing ODM's implementation of these practices, challenging the dominant discourse in similar institutions. The findings of this research demonstrate that the utilization of storytelling and literacy practices at Omah Dongeng Marwah stems from the social and educational conditions in Indonesia, where the behind-the-scenes aspects of theoretical discoveries are often neglected. The effects observed include increased expressiveness among students, enhanced motivation for learning, and the exploration of their talents and interests. Furthermore, through their literacy practices, Omah Dongeng Marwah presents an alternative understanding of school equivalency, asserting that with the flexibility of curriculum development, educational institutions should prioritize meeting the individual needs of students.